2016
DOI: 10.1038/mp.2016.212
|View full text |Cite
|
Sign up to set email alerts
|

Common variants on 2p16.1, 6p22.1 and 10q24.32 are associated with schizophrenia in Han Chinese population

Abstract: Many schizophrenia susceptibility loci have been identified through genome-wide association studies (GWASs) in European populations. However, until recently, schizophrenia GWASs in non-European populations were limited to small sample sizes and have yielded few loci associated with schizophrenia. To identify genetic risk variations for schizophrenia in the Han Chinese population, we performed a two-stage GWAS of schizophrenia comprising 4384 cases and 5770 controls, followed by independent replications of 13 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 50 publications
2
82
1
Order By: Relevance
“…2); rs7596038 is located in the intron region of VRK2 and is predicted to be nonfunctional through the epigenomic analyses using ENCODE data [47], but further studies are necessary to examine its functional impact. Furthermore, in a recent GWAS of SCZ in Han Chinese populations, Yu et al [48] reported that rs1051061 ( r 2 = 0.224 with rs1518395 in Europeans, r 2 = 0.178 with rs1518395 in East Asians) in an exon of VRK2 was genome-wide significantly associated with SCZ in a total of 8,723 cases and 12,813 controls ( p = 1.14 × 10 –12 , see Fig. 1a).…”
Section: Identification Of Vrk2 Variants In Psychiatric Disorders Amomentioning
confidence: 95%
See 3 more Smart Citations
“…2); rs7596038 is located in the intron region of VRK2 and is predicted to be nonfunctional through the epigenomic analyses using ENCODE data [47], but further studies are necessary to examine its functional impact. Furthermore, in a recent GWAS of SCZ in Han Chinese populations, Yu et al [48] reported that rs1051061 ( r 2 = 0.224 with rs1518395 in Europeans, r 2 = 0.178 with rs1518395 in East Asians) in an exon of VRK2 was genome-wide significantly associated with SCZ in a total of 8,723 cases and 12,813 controls ( p = 1.14 × 10 –12 , see Fig. 1a).…”
Section: Identification Of Vrk2 Variants In Psychiatric Disorders Amomentioning
confidence: 95%
“…For example, it is speculated that reduced Vrk2 levels might induce apoptosis [112, 114], thereby affecting normal neurodevelopment during the early stages of life. In fact, Yu et al [48] recently explored the potential functions of Vrk2 in developing mouse brains. They reported that Vrk2 was expressed in the developing cerebral cortex, and the silencing of Vrk2 resulted in the impairment of multipolar–bipolar neuron transition and neural progenitor proliferation [48].…”
Section: Functions Of Vrk2 In the Neurological Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2007, schizophrenia GWAS have been published (for details see http://www.genome.gov/gwastudies). Overall, the studies have failed to support the findings from linkage and candidate gene studies, but the GWAS have instead identified a large number of new susceptibility loci of only very small individual effects—and many of these genomic loci have in fact been replicated in subsequent GWAS and have reached meta-analytic genome-wide significance (see e.g., Shi et al, 2009; Stefansson et al, 2009; Schizophrenia Psychiatric Genome-Wide Association Study Consortium, 2011; Aberg et al, 2013; Ripke et al, 2013; Xiao and Li, 2016; Yu et al, 2016). One seminal study (Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014) combined available schizophrenia GWAS samples into a single analysis and successfully identified 128 independent schizophrenia associations, spanning 108 risk loci of genome-wide significance, 83 of which were novel findings.…”
Section: Molecular Geneticsmentioning
confidence: 99%